Regional Economic Outlook, November 2007, Western Hemisphere. (Regional Economic Outlook; November 2007, 2007)
In spite of a slower U.S. economy and recent market turbulence, growth in the Latin America and Caribbean region has continued at a robust pace. This reports explores the resilience of the LAC region to external shocks and the policy challenges involved in sustaining the region's improved fundamentals. The analysis focuses, in particular, on real and financial linkages with the United States, the strength of underlying fiscal positions, and the sustainability of the ongoing credit boom.